Characterization of cytochrome P450 (CYP) 2D6 drugs as substrates of human organic cation transporters and multidrug and toxin extrusion proteins. (23rd February 2021) - Neul, Claudia; Hofmann, Ute; Schaeffeler, Elke; Winter, Stefan; Klein, Kathrin; Giacomini, Kathleen M.; Eichelbaum, Michel; Schwab, Matthias; Nies, Anne T.
Abstract : Background and Purpose: The metabolic activity of cytochrome P450 (CYP) 2D6 is highly variable and CYP2D6 genotypes insufficiently explain the extensive and intermediate metabolic phenotypes, limiting the prediction of drug response plus adverse drug reactions. Since CYP2D6 prototypic substrates are positively charged, the aim of this study was to evaluate the organic cation transporters (OCTs) and multidrug and toxin extrusion proteins (MATEs) as potential contributors to the variability of CYP2D6 hydroxylation of debrisoquine, dextromethorphan, diphenhydramine, perhexiline and sparteine. Experimental Approach: OCT1/ SLC22A1 ‐, OCT2/ SLC22A2 ‐, OCT3/ SLC22A3 ‐, MATE1/ SLC47A1 ‐, and MATE2K/ SLC47A2 ‐overexpressing cell lines were used to investigate the transport of the selected drugs. Individuals from a study cohort, well defined with respect to CYP2D6 genotype and sparteine pharmacokinetics, were genotyped for the common OCT1 variants rs12208357 (OCT1‐R61C), rs34130495 (OCT1‐G401S), rs202220802 (OCT1‐Met420del), rs34059508 (OCT1‐G465R), OCT2 variant rs316019 (OCT2‐A270S) and MATE1 variant rs2289669. Sparteine pharmacokinetics was stratified according to CYP2D6 and OCT1, OCT2 or MATE1 genotype. Key Results: OCTs and MATE1 transport sparteine and debrisoquine with high affinity in vitro, but OCT‐ and MATE1‐dependent transport of dextromethorphan, diphenhydramine and perhexiline was not detected. Sparteine and debrisoquine transport depends on OCT1 genotype; however, sparteine pharmacokinetics is independent from OCT1 genotype. Conclusions and Implications: Some drugs that are substrates of CYP2D6 are also substrates of OCTs and MATE1, suggesting overlapping specificities. Variability in sparteine hydroxylation in extensive and intermediate metabolizers cannot be explained by OCT1 genetic variants indicating presence of other factors. Dose‐dependent toxicities of dextromethorphan, diphenhydramine and perhexiline appear to be independent from OCTs and MATEs.